Management of sporadic desmoid-type fibromatosis: a European consensus approach based on patients’ and professionals’ expertise : a Sarcoma Patients EuroNet and European Organisation for Research and Treatment of Cancer/Soft Tissue and Bone Sarcoma Group initiative - Kasper, Bernd; Hohenberger, Peter (European journal of cancer, 2015)
Desmoid-type fibromatosis (DF) is a rare monoclonal, fibroblastic proliferation characterised by a variable and often unpredictable clinical course. It may affect nearly all parts of the body including extremities, trunk and abdomen. Considering the variable clinical presentations, anatomic locations and biological behaviours, an individualised treatment approach is required. No established or evidence-based approach for the treatment of this neoplasm is available as of today. Therefore, we propose a consensus treatment algorithm based on a round table meeting bringing together sarcoma experts from the European Organisation for Research and Treatment of Cancer (EORTC) Soft Tissue and Bone Sarcoma Group (STBSG) with patient advocates from Sarcoma Patients EuroNet (SPAEN). The aim of the meeting was to develop - for the first time ever - a consensus approach based on professionals’ AND patients’ expertise. As a fundamental prerequisite, all patients should be discussed in a multidisciplinary setting in centres or professional networks with a specific expertise in the disease.